Traditional Ethics of "HO" Tribe of Saranda Forest Division, Jharkhand - Lal, Hari Shankar; Mishra, P .K. (Indian Forester, 2023)
Jharkhand state is home to a unique diversity of flora which is part of the Gangetic Plain phytogeographical province. It is home to a large number of tribal communities such as; Munda, Oraon, Kharia, Ho and Santhal. Saranda, the land of seven hundred hills of the West Singhbhum district is best known for its Sal (Shorea robusta Roxb) forest and the rich iron ore deposits, supplied to the nearby steel plants. Due to close association of forest, Tribal people are still dependent on the local forest products for their very basic needs, including ethnomedicines. Owing to modernization, habitat destruction and tendency of the younger generation to discard traditional health system most of the ancient knowledge is on the verge of extinction. This thing kept in mind present study enlists the various wild medicinal plant species used by the Tribal and local communities together with their Traditional Knowledge. An extensive survey was carried out of wild medicinal plant species used by Ho tribal people in Saranda Forest Division, west Singhbhum district of Jharkhand. Data were collected through interview questionnaire around the forest division and recorded 273 plant species. All collected plant specimen either in raw material or photograph were deposited in the Department of Botany, Vinoba Bhawe University, Hazaribag.